Mixed convection hybrid nanofluid flow past a non-isothermal cone and wedge with radiation and convective boundary condition: heat transfer optimization - Yahaya, Rusya Iryanti; Md Arifin, Norihan; Mustafa, Mohd Shafie; Pop, Ioan; Md Ali, Fadzilah; Mohamed Isa, Siti Suzilliana Putri (Elsevier, 2025)
This study analyzes the steady hybrid nanofluid flow over a permeable, non-isothermal cone and wedge. The heat transfer analysis considers the effects of thermal radiation and convective boundary conditions. Non-linear ordinary differential equations, derived through similarity transformation of the governing partial differential equations and boundary conditions, are solved numerically using the bvp4c solver. The resulting triple solutions are then subjected to a stability analysis. It is confirmed that only the first solution is stable and physically meaningful, while the other solutions are unstable. The physical quantities of interest, namely the local skin friction coefficient and local Nusselt number, are found to be higher for assisting mixed convection flow than for opposing flow. Compared to the wedge geometry, hybrid nanofluid flow over the cone exhibits a lower local skin friction coefficient but a higher local Nusselt number. Furthermore, optimization results from the response surface methodology (RSM) indicate that the maximum local Nusselt number, corresponding to the highest heat transfer rate at the cone/wedge surface, can be achieved at high values of the Biot number, radiation parameter, and wall temperature parameter.